THE EFFECT OF LEARNING READINESS AND CLIMATE CLASSROOM TOWARD STUDENTS’ LEARNING ACTIVENESS (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2020)
This study aims to determine the effect of learning readiness and classroom climate on students’ activeness both partially and simultaneously. This is quantitative research. The study was conducted at Universitas Indraprasta PGRI, involving 194 students as participants. The data were collected through documentation and online questionnaires using Google form. The results showed that multiple regression analysis was Y = 14.607 + 0,796X1 + 0,344X2. Partially, (t-test) for variable readiness to learn about student learning activeness obtained tcount> 6.132 ttable 0.000 1.9724 with a significance value < 0.005 (Ha accepted) and for classroom climate variables on student learning activeness obtained tcount 4.242 > ttable 1.9724 with a significance value of 0.000 <0.005 (Ha accepted). While simultaneously, (F test) obtained F value of Fcount 49.674> Ftable 3.04 with a significant value of 0.000 < 0.005 (Ha accepted). Therefore, this research reveals several suggestions: (1) students need to prepare themselves well before attending lectures; (2) students need to create a conducive atmosphere for lectures, by building cooperation and solidarity with other classmates; and (3) lecturers provide the broadest possible space for students to express their ideas and thoughts related to learning material.